The Application of Scrapbook Learning Media in Improving Student Engagement and Learning Outcomes in Fiqh: A Classroom Action Research at Al-Hijrah Islamic Boarding School Ngawi - Melati, Difa Rahma; Zarkasyi, Azmi; DIFA RAHMA MELATI, DIFA RAHMA MELATI (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Fiqh learning at the Al-Hijrah Islamic Boarding School in Ngawi still faces obstacles in the form of low student activity and learning outcomes due to the use of less varied methods and the lack of interesting learning media. This is evident from the average initial grade of grade 1 in the 2024/2025 academic year which only reached 3.8 and did not meet the completion criteria. This study aims to describe the application of Scrapbook media and analyze the increase in student activity and learning outcomes in Fiqh. This study uses the Classroom Action Research (CAR) method using the Kemmis and McTaggart model which was implemented in two cycles through the stages of planning, implementation, observation, and reflection. The research subjects were 43 students in grade 1. Data were collected through observation, written tests, and documentation, then analyzed descriptively quantitatively with percentages and comparisons between cycles supported by qualitative analysis. The results of the study showed an increase in learning activity from 48.8% in cycle I to 77.2% in cycle II, as well as an increase in the completion of learning outcomes from 46.5% to 100%. These findings indicate that Scrapbook media is effective in increasing female students' active participation and understanding of Fiqh material through visual, engaging, and interactive presentation. Thus, Scrapbooks can be an effective alternative learning medium for improving the quality of learning processes and outcomes.